Contribuições das bases da neurociência e categorias da psicologia histórico-cultural no processo de alfabetização - Brito, Cleide Morais Leonaldo de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The theme of this research is literacy optimized by the bases of Neuroscience, developed by the dialectical method. This is a theoretical work that has as objects of research, the process of Literacy, the bases of Neuroscience, the configuration of the Dialectic Method and the theoretical assumptions of Psychology - Cultural History. The purpose is to demonstrate the interconnections between these research objects. The questions that guided this research were: What are the contributions of the bases of Neuroscience to the literacy process? How can Historical-Cultural Psychology help methodologically in literacy? Thus, it was established as a general objective to use bases of Neuroscience and methodological foundations of Historical-Cultural Psychology to optimize the literacy process. As specific objectives, we have: 1) to point out the elements that constitute the bases of Neuroscience; 2) to identify the dialectic categories that allow the process of internalization of the object under study (literacy) and 3) to elaborate a modeling in a lesson plan format that outlines the convergence of the Neuroscience, Historical-Cultural Psychology and Language (literacy) theories In the dialectical method. The established concepts were the relations between psychic functions, central nervous system, dialectical method (dialectical units), grapheme-phoneme, symbol-meaning, content-form

O tema desta pesquisa é a alfabetização otimizada pelas bases da Neurociência, desenvolvido pelo método dialético. Este é um trabalho teórico que tem como objetos de pesquisa, o processo de Alfabetização, as bases da Neurociência, a configuração do Método Dialético e os pressupostos teóricos da Psicologia - Histórico Cultural. Tem-se como finalidade demonstrar as interligações entre esses objetos de pesquisa. As questões que nortearam esta pesquisa foram: Quais as contribuições das bases da Neurociência para o processo de alfabetização? Como a Psicologia Histórico-Cultural pode auxiliar metodologicamente na alfabetização? Assim, estabeleceu-se como objetivo geral utilizar bases da Neurociência e fundamentos metodológicos da Psicologia Histórico-Cultural para otimizar o processo de alfabetização. Como objetivos específicos, tem-se: 1) apontar os elementos que constituem as bases da Neurociência; 2) identificar as categorias dialéticas que possibilitam o processo de internalização do objeto em estudo (alfabetização) e 3) elaborar uma modelagem em formato de plano de aula que esboça a convergência das teorias Neurociência, Psicologia Histórico-Cultural e Língua (alfabetização), pautada no método dialético. Os conceitos estabelecidos foram as relações entre funções psíquicas, sistema nervoso central, método dialético (unidades dialéticas), grafema-fonema, símbolo-significado, conteúdo-forma
Keywords: Neurociências; Psicologia; Alfabetização; Neurosciences